Adequate nephroprotection reduces renal complications after hyperthermic intrathoracic chemotherapy. Issue 7 (10th October 2019) - Markowiak, Till; Kerner, Nadine; Neu, Reiner; Potzger, Tobias; Großer, Christian; Zeman, Florian; Hofmann, Hans‐Stefan; Ried, Michael
Abstract: Background and Objectives: Hyperthermic intrathoracic chemotherapy (HITOC) is used for the treatment of malignant pleural tumors. Although HITOC proved to be safe, postoperative renal failure due to nephrotoxicity of intrapleural cisplatin remains a concern. Methods: This single‐center study was performed retrospectively in patients who underwent pleural tumor resection and HITOC between September 2008 and December 2018. Results: A total of 84 patients (female n  = 33; 39.3%) with malignant pleural tumors underwent surgical cytoreduction with subsequent HITOC (60 minutes; 42°C). During the study period, we gradually increased the dosage of cisplatin (100–150 mg/m 2 BSA n = 36; 175 mg/m 2 BSA n = 2) and finally added doxorubicin (cisplatin 175 mg/m 2 BSA/doxorubicin 65 mg; n = 46). All patients had perioperative fluid balancing. The last 54 (64.3%) patients also received perioperative cytoprotection. Overall 29 patients (34.5%) experienced renal insufficiency. Despite higher cisplatin concentrations, patients with cytoprotection showed significantly lower postoperative serum creatinine levels after 1 week ( P  = .006) and at discharge ( P  = .020). Also, they showed less intermediate and severe renal insufficiencies (5.6% vs 13.3%). Conclusions: Adequate perioperative fluid management and cytoprotection seem to be effective in protecting renal function. This allows the administration of higher intracavitary cisplatin doses without raising the rate of renal insufficiencies.